THROMBOPOIETIN RECEPTOR AGONISTS IN THE TREATMENT OF PRIMARY IMMUNE THROMBOCYTOPENIA: OUR EXPERIENCE - Golubović, Ivana (Acta medicae Medianae, 2024)
The primary immuna thrombocytopenia (ITP) is an acquired autoimmune disease characterized by isolated thrombocytopenia PLT < 100 x 109/L, and the absence of all conditions and diseases that can result in thrombocytopenia. The first-line therapy in ITP involves the use of corticosteroids, intravenous immunoglobulin or an immunoglobulin anti-D. The second-line treatment includes splenectomy, immunosuppressive drugs and agonists of thrombopoietin receptor (TPO-RA). To describe the treatment results with TPO-RA (eltrombopagin patients with ITP in the Clinic of Hematology UCC NIš. Between March 2018 and December 2023, at the Clinic of Hematology UCC Niš, 6 patients with ITP in which the previous treatment lines did not respond to the therapy or gave side effects were treated with TRO-RA. The indication for the TRO-RA therapy was chronic ITP. The period from the diagnosis to the initiation of the treatment with TRO-RA was on average 71,5 months. The analysis of the average number of platelets after TPO-RA therapy showed an upward trend. The TPO-RA does not show immunosuppression, they lead to an increase in platelet count, stopping bleeding and improving the quality of life. Therefore, TPO-RA are essential medicines for the treatment of ITP after the failure of the first and second - line therapy.